Individual- and neighborhood-level education influences the effect of obesity on prostate cancer treatment failure after prostatectomy - Zeigler-Johnson, Charnita (Cancer Causes Control, 2015)
PURPOSE: The relationship between obesity and prostate cancer (CaP) treatment failure is complex and may vary by patient- and neighborhood-level educational attainment. We evaluated whether patient- and neighborhood-level education is associated with the effect of obesity on biochemical recurrence. METHODS: Seven hundred and forty-six CaP cases were classified into four groups: Concordant Low–Low: less educated cases (<4 years college) living in a less educated neighborhood (below-median proportion of college-educated residents; n = 164); Concordant High–High: highly educated cases (≥4 years college) living in a highly educated neighborhood (above-median proportion of college-educated residents; n = 326); Discordant Low–High: less educated cases living in a highly educated neighborhood (n = 69); and Discordant High–Low: highly educated cases living in a less educated neighborhood (n = 187). Cox regression models were used to examine associations between obesity and biochemical (PSA) failure after prostatectomy stratified by the concordant/discordant groups. RESULTS: The association of obesity with biochemical failure varied significantly by educational concordance/discordance (p = 0.007). Obesity was associated with risk of biochemical failure for less educated cases residing in less educated neighborhoods (HR 3.72, 95 % CI 1.30–10.65). The relationship was not significant for other concordant/discordant groups. CONCLUSIONS: Obesity effects on CaP outcomes vary by multilevel educational discordance/concordance. Strategies to decrease prostate cancer risk of progression may focus on reduction in obesity, particularly for less educated cases residing in less educated neighborhoods.